WDPhotTools – a white dwarf photometric toolkit in Python. Issue 1 (8th December 2022) - Lam, M C; Yuen, K W; Green, M J; Li, W
Abstract: From data collection to photometric fitting and analysis of white dwarfs, to generating a white dwarf luminosity function requires numerous astrophysical, mathematical, and computational domain knowledge. The steep learning curve makes it difficult to enter the field, and often individuals have to reinvent the wheel to perform identical data reduction and analysis tasks. We have gathered a wide range of publicly available white dwarf cooling models and synthetic photometry to provide a toolkit that allows (i) visualization of various models, (ii) photometric fitting of a white dwarf with or without distance and reddening, and (iii) the computing of white dwarf luminosity functions with a choice of initial mass function, main-sequence evolution model, star-formation history, initial–final mass relation, and white dwarf cooling model. We have recomputed and compared the effective temperature of the white dwarfs from the Gaia EDR3 white dwarf catalogue. The two independent works show excellent agreement in the temperature solutions.